Peran Kepala Sekolah Dalam Meningkatkan Disiplin Kerja Guru Di Sekolah Dasar Negeri 04/Vii Sarkam 1 - Bayu Prayudi (Jurnal Dinamika Manajemen, 2016)
The purpose of this study was to find out and analyze the role of the school principal in improving the work discipline of teachers at Public Elementary School Number 40/VII Sarkam 1. The method used is to use a type of qualitative research, which is a research method used to examine the condition of natural objects, and writers are key instruments. The data collection technique was carried out by means of triangulation (combined), data analysis is inductive in nature and the results of qualitative research emphasize the meaning of generalization patterns. The results of the study concluded that the increase in Teacher Work Discipline at Public Elementary School 04/VII Sarolangun Kembang 1 namely, the role of the Principal in improving Teacher Work Discipline, the first by formulating the Vision and Mission relating to the Teacher work Discipline, the second, namely by holding meetings at the end of each month, the third is by supervising and reprimanding, then by providing motivation to all Elementary School Personnel in Negei 04/VII Sarolangun Kembang 1. The factors that influence work discipline are the needs that school personnel feel are not being met. Then the actions taken were giving reprimands, coaching, and in a big way the role of the Principal in Improving Teacher Work Discipline at Public Elementary School 04/VII Sarolangun Kembang 1, Sarolangun District, namely that he was good enough to carry out the role of school principal. But there are still obstacles that must be removed immediately.